2009
DOI: 10.1007/s00542-009-0981-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultra light-weight and high-resolution X-ray mirrors using DRIE and X-ray LIGA techniques for space X-ray telescopes

Abstract: We are developing novel ultra light-weight and high-resolution X-ray micro pore optics for space X-ray telescopes. In our method, curvilinear micro pore structures are firstly fabricated by silicon deep reactive ion etching (DRIE) or X-ray LIGA processes. Secondly, side walls of the micro structures are smoothed by magnetic field assisted finishing and/or hydrogen annealing techniques for high reflectivity mirrors. Thirdly, to focus parallel X-ray lights from astronomical objects, these structures are elastica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 14 publications
1
41
0
1
Order By: Relevance
“…Figure 45 (right panel) shows a micrograph picture of the channel structure of a square-packed MPO plate. Ezoe et al (2009) reported using micromachining technologies to etch the curvilinear micropore sidewalls through a thin silicon wafer for use as reflecting surfaces. As with the MPOs, two such wafers deformed to different curvatures of radii can be stacked to work in the Wolter geometry.…”
Section: Optical Elementsmentioning
confidence: 99%
“…Figure 45 (right panel) shows a micrograph picture of the channel structure of a square-packed MPO plate. Ezoe et al (2009) reported using micromachining technologies to etch the curvilinear micropore sidewalls through a thin silicon wafer for use as reflecting surfaces. As with the MPOs, two such wafers deformed to different curvatures of radii can be stacked to work in the Wolter geometry.…”
Section: Optical Elementsmentioning
confidence: 99%
“…, that is, structures with a large height/width ratio, have found many applications 1,2 such as X-ray gratings 3 , gas chromatography columns 4 , magnetic coils 5 , X-ray telescopes 6 , micro-gears 7 , micro-capacitors with highaspect-ratio (HAR) cantilevers 8 , and micromechanical and microoptical elements 9,10 . These structures exhibit aspect ratios (ARs) of over 10 and almost vertical sidewalls, making them much more challenging to develop than the structures typically used in planar technology with moderate ARs of 1 to 2.…”
Section: High-aspect-ratio Microstructures (Harms)mentioning
confidence: 99%
“…Furthermore, it will also result in an increase in optical losses in the development of the proposed PNFs. To prevent this, silicon cryo-etch has been used with an SF 6 :O 2 plasma 16 . This method uses low temperatures (typically below − 100°C) at which a passivating layer of SiO x F y is formed.…”
Section: Silicon-based Masters and Mouldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final type is our micromachined X-ray optics, which utilizes tiny micro pores through a thin silicon wafer for X-ray mirrors (Ezoe et al 2010). Because the narrow micro pores enabled by the microelectromechanical systems (MEMS) technologies, this can be one of the lightest X-ray telescopes ever achieved.…”
Section: Introductionmentioning
confidence: 99%